Increasing of radiographic clinical value by using of Radio Photo Electrostatic imaging system (Xeroradiography) - Navvabpour, Mojtaba; Navvabpour, Naeima (Archives of Advances in Biosciences, 2012)
Ordinary Radiographic film sensitive emulsion is formed by crystals which are composed by millions of ions. According to the film texture, image constructive units number that interfere the image resolution are not increased more than a certain limitation in area unite. This innovation is to present an imaging system that to compare with common similar system has precedence such as highly image resolution, image edge sharpnessenhancement, contrast improvement, patient does reduction, rapid processing and cost decrease. The "Xero" technique is different physical method for imaging procedures in which instead of using the photochemical function, electrostatic effect has been used. The latent electrostatic images develop through toner powder, Because the toner powder particles are fine grain as small as a few compound molecules, Consequently, in the new method, image constructive units number which are described as the toner powder particles are much many more in number than crystals of radiographic films. Xeroradiophotography system is designed and constructed based on xero physical phenomenon in which image can be formed by taking advantage of both, X-Ray and visible light complex procedure for the purpose of X-Rays quality and patients body tissue side effect reduction at the time of exposure. This system has already been made as the first archetype in the world that is possible for optimum improving soon.